2022
DOI: 10.1152/japplphysiol.00734.2021
|View full text |Cite
|
Sign up to set email alerts
|

From heart to muscle: pathophysiological mechanisms underlying long-term physical sequelae from SARS-CoV-2 infection

Abstract: The long-term sequelae of the coronavirus disease 2019 (COVID-19) are multifaceted and, besides the lungs, impact other organs and tissues, even in cases of mild infection. Along with commonly reported symptoms such as fatigue and dyspnea, a significant proportion of those with prior COVID-19 infection also exhibit signs of cardiac damage, muscle weakness, and ultimately, poor exercise tolerance. This review provides an overview of evidence indicating cardiac impairments and persistent endothelial dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 92 publications
(144 reference statements)
1
20
0
2
Order By: Relevance
“…Its pathophysiology mainly involves direct virus-mediated cell damage, endothelial and microvascular injury, and hyperinflammatory response ( 1 ). These acute mechanisms can lead to a spectrum of clinical manifestations ranging from gas-exchange abnormalities to cardiovascular and mitochondrial dysfunction ( 2 , 3 ). In its post-acute phase, the long-lasting effects of the disease include symptoms such as fatigue, dyspnea, and muscle weakness ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its pathophysiology mainly involves direct virus-mediated cell damage, endothelial and microvascular injury, and hyperinflammatory response ( 1 ). These acute mechanisms can lead to a spectrum of clinical manifestations ranging from gas-exchange abnormalities to cardiovascular and mitochondrial dysfunction ( 2 , 3 ). In its post-acute phase, the long-lasting effects of the disease include symptoms such as fatigue, dyspnea, and muscle weakness ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…These acute mechanisms can lead to a spectrum of clinical manifestations ranging from gas-exchange abnormalities to cardiovascular and mitochondrial dysfunction ( 2 , 3 ). In its post-acute phase, the long-lasting effects of the disease include symptoms such as fatigue, dyspnea, and muscle weakness ( 3 ). At the same time, COVID-19 survivors often develop exertional intolerance, presenting with reduced exercise capacity ( 4 , 5 ), the etiology of which is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of restoring their functional capacity seems particularly important for patients who have survived hospitalizations, since half of them present severely impaired physical functioning and a drastically reduced ability to perform daily activities after discharge [ 25 ]. Yet, not only for severe but also for mild forms of the disease, PA might help prevent the risk of complication, reduce the risk of long-lasting disability, and reintroduce patients to their own pre-COVID-19 life [ 26 , 27 , 28 , 29 , 30 , 31 ]. Although there is an impressive number of reviews or recommendation papers mentioning the interest in PA as part of COVID-19 rehabilitation, only a limited amount of clinical evidence is available.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 12 Other studies have suggested that symptoms of long‐COVID, specifically the non‐respiratory symptoms, are due to persistent endothelial dysfunction. 13 , 14 Finally, many studies have shown that the current pandemic has had detrimental psychological impacts on all human populations, including those with cured COVID‐19. 15 , 16 , 17 These psychiatric problems have significant associations with some of the subjective symptoms that are reported by patients with long‐COVID (e.g.…”
Section: Discussionmentioning
confidence: 99%